The effects of political policies in the United States and the relation to foreign direct investment - Bonwell, Jacob (My University, 2025)
Foreign Direct Investments (FDI) play a significant role in shaping economic growth. This thesis explores how the political landscape of the United States impacts Foreign Direct Investments. Specifically, how liberal or conservative leaning policies influence the increasing or decreasing of Net FDI inflows. This paper explores the complex relationship between FDI inflows, key macroeconomic factors, a political leaning index, and the effect of the variables on net FDI inflows into the United States. Using a linear regression model, this study reports on the analysis FDI data over the course of 23 years from 2000 to 2022. The economic indicators selected to influence FDI include inflation, exchange rates, GDP per capita, lagged net FDI inflows, and a political leaning index—specific to the United States economy. Results indicate that macroeconomic factors of exchange rates, inflation, and GDP per capita, have a statistically significant influence on net FDI inflows, whereas the political policy index indicates no statistical or economic correlation. Contrary to the initial hypothesis, the findings suggest that macroeconomic conditions, shaped by policies implemented by policy makers in power at that time play a more critical role in determining FDI trends than overt liberal/conservative policies. The results suggest that historical business strategy was better of prioritizing economic indicators over sharp political disparities when evaluating FDI opportunities. For policymakers, promoting a stable economic environment may be more effective in attracting foreign investment than focusing solely on political policies. Future research should explore sector-specific influences and international comparisons to deepen the understanding of FDI factors.
Keywords: Foreign Direct Investment; Political policies; Investment motivations; Inflows; Outflows